Correlates of polyneuropathy in Parkinson’s disease - Kühn, Eva (Ann Clin Transl Neurol, 2020)
OBJECTIVE: Previous studies in Parkinson’s disease (PD) patients have demonstrated a high prevalence of polyneuropathy (PNP) and pronounced alpha‐Synuclein pathology in dermal nerve fibers already at early disease stages. The aim of this study was to analyze associations between the prevalence and severity of PNP with nonmotor and motor symptoms in PD patients. METHODS: Fifty PD patients were characterized comprehensively for the presence of clinical symptoms (nonmotor and motor), electrophysiologic alterations and – for the first time – using high‐resolution ultrasound of peripheral nerves. RESULTS: Sixty‐two percent of PD patients showed electrophysiological pathology of PNP. The prevalence of patient‐reported PNP symptoms was 86% and was particularly present in patients with longer disease duration, compromised scores of nonmotor and motor symptoms as well as with a negative evaluation of quality of life. Seventy‐five percent of patients showed morphologic alterations similar to axonal PNP in high‐resolution ultrasound compared to healthy controls. INTERPRETATION: The study demonstrates the high burden of peripheral nervous system disease in Parkinson's disease. It advocates further studies to delineate the underlying pathophysiological mechanisms in order to optimize treatment approaches for PD, including the associated PNP.